2008
DOI: 10.1371/journal.pmed.0050179
|View full text |Cite
|
Sign up to set email alerts
|

Revision Rates after Primary Hip and Knee Replacement in England between 2003 and 2006

Abstract: BackgroundHip and knee replacement are some of the most frequently performed surgical procedures in the world. Resurfacing of the hip and unicondylar knee replacement are increasingly being used. There is relatively little evidence on their performance. To study performance of joint replacement in England, we investigated revision rates in the first 3 y after hip or knee replacement according to prosthesis type.Methods and FindingsWe linked records of the National Joint Registry for England and Wales and the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…This information fills an important knowledge gap and suggests that revision-free survival may have improved over time. These revision-free survival rates in patients with shoulder hemiarthroplasty are slightly lower than those reported after knee and hip replacement surgeries 1; 10 .…”
Section: Discussionmentioning
confidence: 54%
“…This information fills an important knowledge gap and suggests that revision-free survival may have improved over time. These revision-free survival rates in patients with shoulder hemiarthroplasty are slightly lower than those reported after knee and hip replacement surgeries 1; 10 .…”
Section: Discussionmentioning
confidence: 54%
“…Our results confirm those reported by Vendittoli et al [38], who evaluated blood ion concentrations in patients with MOM Durom hip resurfacing (Zimmer, Winterthur, Switzerland). Concerns have been raised regarding a substantially greater failure rate in females treated with MOM-BHR compared with males [7,32]. Vendittoli et al [38] suggested that female gender contributed to higher metal ion levels with resurfacing implants.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HES these systems normally attract a high level of clinical engagement and some of them have benefited from linkage to HES. 15 However, these data are not comprehensive, leading to a situation where some practitioners have excellent information about their service including the quality of patient care and others have none. The benefit of high-quality clinical data has been demonstrated by the year-on-year improvements in outcome following a cardiac surgery.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%